Perception about newly launched CBDC by RBI in South Mumbai region (International Journal of Food and Nutritional Sciences, 2022)
World is going through rapid transformation in financial sector reforms along with dynamic innovation changing the way financial transactions are carried out. There were days when people used to consider digital payment methods & digitization of the economy with reference to the Indian context an impossible affair. The one big move in the series of digital innovations after UPI is CBDC. It refers to Central Bank Digital Currency. CBDC is an important tool in the future digitized economy and will play a vital role in providing a competitive advantage to countries with strong technological infrastructure. The digital wave and growing crypto trend were also key factors forcing central banks to explore this horizon. The growing preference of investors in crypto created various concerns for central banks, like funding illegal activities, development of a parallel economy, financial instability, and many more. Across the globe, approximately nine countries have already launched CBDC, out of which eight countries are located in Caribbean. Nigeria is the first country in Africa to launch CBDC in the form of e-Naira. Apart from this, more than 100 countries are exploring the opportunities to launch CBDC in their country. India, one of the fastest developing economies globally, has also launched CBDC at a pilot stage to study its impact and the benefits it can offer to the Indian economy in the coming years. Reserve Bank of India has launched a pilot for wholesale transactions on 1st November 2022 and for retail transactions on 1st December 2022. A retail pilot is carried out in cities like Mumbai, Delhi, Bengaluru and Bhuvneshwar. Then subsequently adding different cities of the country. This paper looks forward to addressing people's perception of CBDC in the South Mumbai region.